2012
DOI: 10.1126/scisignal.2002858
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogenes: Newly Discovered Players in Human Cancer

Abstract: Because they are generally noncoding and thus considered nonfunctional and unimportant, pseudogenes have long been neglected. Recent advances have established that the DNA of a pseudogene, the RNA transcribed from a pseudogene, or the protein translated from a pseudogene can have multiple, diverse functions and that these functions can affect not only their parental genes but also unrelated genes. Therefore, pseudogenes have emerged as a previously unappreciated class of sophisticated modulators of gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 174 publications
(233 reference statements)
0
112
0
Order By: Relevance
“…B-caused downregulation of A-located genes is likely mediated by mechanisms that have been postulated for pseudogenes of other species. A growing body of evidence strongly suggests a role for pseudogenes in regulating parental gene expression by serving as a source of endogenous siRNA and antisense transcripts as competitive inhibitors of translation of wild-type transcripts and of sequestering microRNAs (reviewed in Poliseno, 2012). Another possibility for how Bs could exert control on As is their effect on the spatial interphase organization of the genome itself.…”
Section: B-located Pseudogene-like Fragments Contribute To the Transcmentioning
confidence: 99%
“…B-caused downregulation of A-located genes is likely mediated by mechanisms that have been postulated for pseudogenes of other species. A growing body of evidence strongly suggests a role for pseudogenes in regulating parental gene expression by serving as a source of endogenous siRNA and antisense transcripts as competitive inhibitors of translation of wild-type transcripts and of sequestering microRNAs (reviewed in Poliseno, 2012). Another possibility for how Bs could exert control on As is their effect on the spatial interphase organization of the genome itself.…”
Section: B-located Pseudogene-like Fragments Contribute To the Transcmentioning
confidence: 99%
“…By definition, pseudogenes are dysfunctional counterparts of genes that have lost protein-coding potential due to accumulation of mutations during genome evolution. 25 They are generally identified by computational analysis of genomic sequences using complex algorithms and are characterized by homology to a known gene and nonfunctionality. 26 It is estimated that the human genome contains more than 18,000 pseudogenes.…”
Section: Classification Of Distinct Lncrnas Based On Their Genomic Comentioning
confidence: 99%
“…27 More and more evidence suggests that pseudogenes may have physiological significance by their direct interactions with DNA or transcripts of the parental protein-coding genes. 25 Recently, it was revealed that the mRNA levels of the tumor suppressor PTEN and oncogenic KRAS are regulated by their pseudogenes PTENP1 and KRASP1, attributing a novel biological role to expressed pseudogenes in cancer progression. 28 Four) Long intronic ncRNAs.…”
Section: Classification Of Distinct Lncrnas Based On Their Genomic Comentioning
confidence: 99%
“…Examples of full-length pseudogenic proteins do exist. However, short pseudogenic peptides are more common [ 11 ] and their unequivocal annotation represents a very interesting subject of investigation.…”
Section: Introductionmentioning
confidence: 99%